Low-canopy seagrass beds still provide important coastal protection services. - Marjolijn J A Christianen; Jim van Belzen; Peter M J Herman; Marieke M van Katwijk; Leon P M Lamers; Peter J M van Leent; Tjeerd J Bouma (PLoS ONE, 2013)
One of the most frequently quoted ecosystem services of seagrass meadows is their value for coastal protection. Many studies emphasize the role of above-ground shoots in attenuating waves, enhancing sedimentation and preventing erosion. This raises the question if short-leaved, low density (grazed) seagrass meadows with most of their biomass in belowground tissues can also stabilize sediments. We examined this by combining manipulative field experiments and wave measurements along a typical tropical reef flat where green turtles intensively graze upon the seagrass canopy. We experimentally manipulated wave energy and grazing intensity along a transect perpendicular to the beach, and compared sediment bed level change between vegetated and experimentally created bare plots at three distances from the beach. Our experiments showed that i) even the short-leaved, low-biomass and heavily-grazed seagrass vegetation reduced wave-induced sediment erosion up to threefold, and ii) that erosion was a function of location along the vegetated reef flat. Where other studies stress the importance of the seagrass canopy for shoreline protection, our study on open, low-biomass and heavily grazed seagrass beds strongly suggests that belowground biomass also has a major effect on the immobilization of sediment. These results imply that, compared to shallow unvegetated nearshore reef flats, the presence of a short, low-biomass seagrass meadow maintains a higher bed level, attenuating waves before reaching the beach and hence lowering beach erosion rates. We propose that the sole use of aboveground biomass as a proxy for valuing coastal protection services should be reconsidered.